Influence of Cryogenic Grinding on the Nutritional and Antinutritional Components of Rapeseed Cake - Klara Kraljić; Dubravka Škevin; Nikolina Čukelj Mustač; Maja Benković; Saša Drakula; Sandra Balbino; Ana Mandura Jarić; Karla Mamilović; Ivana Ramljak; Duška Ćurić (Applied Sciences, 2023)
We investigated the influence of cryogenic grinding on the quality of rapeseed cake. Rapeseed cake is a good source of valuable proteins (30%) and oil (14%), with a balanced fatty acid composition and a fair amount of sterols, which may reduce the risk of cardiovascular diseases. However, the presence of antinutritive compounds prevents its use as a food source. Grinding under cryogenic conditions is much more efficient than grinding at room temperature in terms of particle size reduction. The additional cryogenic grinding of the cake had little effect on the nutritional components, as phytosterols and soluble dietary fiber increased slightly. It had no effect on insoluble dietary fiber, polyphenols, and tannins. Prolonged grinding time, both at room and subzero temperatures, reduced the total amount of glucosinolates by 34 and 43%, respectively. However, the reduction in undesirable components is not sufficient to use cryogenic grinding as the sole treatment for the cake, but it could be a good pretreatment for chemical or biological treatments.